Management of Character Education in the Development of Leading High School Students - Zainal Ilmi; Ulfiah Ulfiah; Sayid Muhammad Rifqi Noval; Usep Kosasih (International Journal of Nusantara Islam, 2019)
This research entitled "Character Education Management in the Development of High School Students' Noble Morals (Qualitative Descriptive Study in SMAN 1 and SMA Islam Qardhan Hasana Kota Banjar Baru)". This study aims to determine and analyze: (1) Planning, (2). Organizing (3). Implementation (4). Evaluation (5). Barriers to implementation (7) Solutions to implementation problems. Three important foundations are used in this research, including theological, philosophical, and six value systems. The theories that underlie this research are management theory and quality theory. This research uses a qualitative approach with descriptive methods. Data collection was carried out by triangulation techniques using interviews, document study, and field observations. With research subjects the principal, teacher. Data analysis was carried out through data reduction, data presentation, and conclusions. The main findings of this study were: (1) The planning of character education in the development of noble character in high school has been structured quite well and systematically, but its implementation still faces several obstacles, namely human resources (2). Organizing has been running according to the program with the same principles of understanding, responsible commitment, although not yet supported by adequate job analysis. (3) Implementation has gone well. However, it has not paid attention to the resources owned. (4) Evaluation according to the school work program in the future, however, it has not been followed up with innovative programs that are in accordance with the needs. (5) Obstacles in implementation can be implemented although not evenly distributed (7) . Solutions in implementation can be done to overcome obstacles through a process of coaching and development. Recommendations for this study were conveyed to various parties, including the Principal, so that planning was supported by adequate teacher resources. Organizing should first conduct a job analysis. Implementation should pay attention to the resources owned in order to achieve targets effectively and efficiently. Evaluation is recommended to pay attention to the results obtained during the implementation so that the program is sustainable. It is recommended that teachers continue to improve competencies, both pedagogical, social, personal and professional competencies.